Analisa Pengendalian Waktu Dan Biaya Proyek ITC Pole Fibre Optic Menggunakan Metode Earned Value: Studi Kasus: PT.LUM - Indra Bakti; Mohamad Firdaus (Switch : Jurnal Sains dan Teknologi Informasi, 2023)
This research aims to analyze time and cost control on the ITC Pole Fiber Optic project managed by PT. LUM uses the Earned Value Management (EVM) method. EVM is an effective method for measuring project performance and progress by combining cost, time and completed work data. This case study uses secondary data obtained from project progress reports and PT financial data. LUM. Analysis is carried out to identify cost variance (CV) and schedule variance (SV) as well as cost performance index (CPI) and schedule performance index (Schedule Performance Index - SPI). The research results show that the ITC Pole Fiber Optic project experienced several deviations from the planned budget and schedule, with CV and SV showing negative values ​​at several project stages, indicating cost overruns and delays. The CPI and SPI values ​​obtained also provide an overview of the efficiency and effectiveness of project implementation. Based on these findings, several improvement steps are recommended to optimize time and cost control to improve project performance in the future. This research makes an important contribution in providing insight into the application of EVM in fiber optic installation projects and can be used as a reference in managing similar projects in the future.